Detection of periprosthetic fractures around the femoral stem by resonance frequency analysis: An in vitro study. (May 2023) - Poudrel, Anne-Sophie; Rosi, Giuseppe; Nguyen, Vu-Hieu; Housset, Victor; Flouzat-Lachaniette, Charles-Henri; Haiat, Guillaume
Periprosthetic femoral bone fractures are frequent complications of Total Hip Arthroplasty (THA) and may occur during the insertion of uncemented Femoral Stems (FS), due to the nature of the press-fit fixation. Such fracture may lead to the surgical failure of the THA and require a revision surgery, which may have dramatic consequences. Therefore, an early detection of intra-operative fractures is important to avoid worsening the fracture and/or to enable a peroperative treatment. The aim of this in vitro study is to determine the sensitivity of a method based on resonance frequency analysis of the bone-stem-ancillary system for periprosthetic fractures detection. A periprosthetic fracture was artificially created close to the lesser-trochanter of 10 femoral bone mimicking phantoms. The bone-stem-ancillary resonance frequencies in the range (2–12) kHz were measured on an ancillary instrumented with piezoelectric sensors, which was fixed to the femoral stem. The measurements were repeated for different fracture lengths from 4 to 55 mm. The results show a decrease of the resonance frequencies due to the fracture occurrence and propagation. The frequency shift reached up to 170 Hz. The minimum fracture length that can be detected varies from3 . 1 ± 1 . 7  mm to5 . 9 ± 1 . 9  mm according to the mode and to the specimen. A significantly higher sensitivity ( p  = 0.011) was obtained for a resonance frequency around 10.6 kHz, corresponding to a mode vibrating in a plane perpendicular to the fracture. This study opens new paths toward the development of non-invasive vibration-based methods for intra-operative periprosthetic fractures detection.